2000
DOI: 10.1080/074811800200667
|View full text |Cite
|
Sign up to set email alerts
|

Adults Mourning Suicide: Self-Reported Concerns About Bereavement, Needs for Assistance, and Help-Seeking Behavior

Abstract: This study empirically characterized the experiences of 227 adult next-of-kin as they mourned suicides that had occurred in New York City during 1997. Next-of-kin reported psychosocial problems including family difficulties, comorbid stressors, psychiatric symptomatology, and unresolved bereavement. Professional intervention was the most frequently reported need and the most frequently reported type of desired help. In terms of actual receipt of assistance, participants reported having received help from fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…Suicide is clearly a significant public health issue (US Public Health Service, 2002). Each suicide produces at least six and as many as hundreds of “survivors,” those people who are left behind to grieve and make sense of the death (American Foundation for Suicide Prevention, 2004; Crosby & Sacks, 2002; Provini, Everett, & Pfeffer, 2000). While the word survivor tends to be used in The United States of America, in other parts of the world, “bereaved by suicide” is a more widely used term (Beautrais, 2004).…”
Section: Public Health Priorities: Suicide and Its Destructive Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicide is clearly a significant public health issue (US Public Health Service, 2002). Each suicide produces at least six and as many as hundreds of “survivors,” those people who are left behind to grieve and make sense of the death (American Foundation for Suicide Prevention, 2004; Crosby & Sacks, 2002; Provini, Everett, & Pfeffer, 2000). While the word survivor tends to be used in The United States of America, in other parts of the world, “bereaved by suicide” is a more widely used term (Beautrais, 2004).…”
Section: Public Health Priorities: Suicide and Its Destructive Effectsmentioning
confidence: 99%
“…Only about 25 percent of 144 next-of-kin survivors surveyed by phone reported receiving any help since the suicide, despite seventy-four percent indicating a desire for help (Provini, et al, 2000). In another study, half of Norwegian bereaved survivors felt a need for professional mental health treatment, but only one quarter actually sought out help (Dyregrov, 2002).…”
Section: Public Health Priorities: Suicide and Its Destructive Effectsmentioning
confidence: 99%
“…A study by Provini et al . [23] showed that while 72% of survivors expressed the need for professional help, only 47% actually received it; an observation confirmed in other studies, e.g., [32]. It has been estimated that while there were over 50,000 suicides per year in Europe, only 10,000 survivors attended survivor groups and there are significant differences in the availability of this form of help in Europe.…”
Section: What Is “Postvention” and What Are The Needs Of Suicide Smentioning
confidence: 70%
“…A wide variety of psycho-social needs of suicide survivors which should be met by postvention programs have been identified. These include difficulties related to the disruption of family relations and routines, functional impairments in daily activities, difficulties with social and familial relationships, spiritual struggles as well as financial and juridical problems [10,20,21,22,23]. In addition, the mechanisms of identification with the deceased, social modelling, punishment for perceived self-blame as well as genetic factors might be accountable for the increased risk of suicidal ideation and behaviour, and at-risk behaviours observed among some of the survivors [24].…”
Section: What Is “Postvention” and What Are The Needs Of Suicide Smentioning
confidence: 99%
“…Possibly, this has affected their attitudes and proceedings regarding relatives’ help requests. This assumption is supported by the large proportion of GPs (65%) who counselled the bereaved themselves; more often than a ∼50% rate found in previous studies 25. Unfortunately, it remained unclear to what extent the sample represents GPs who were actually involved in the RCT.…”
Section: Discussionmentioning
confidence: 92%